2021
DOI: 10.3727/216929721x16105303036562
|View full text |Cite
|
Sign up to set email alerts
|

What is the Role of Demographics in Tourists' Attitudes Towards Foods?

Abstract: This study examines the demographic factors affecting food involvement and food awareness of tourists. Data were collected from potential Chinese tourists (n = 580) via questionnaire using a purposive sampling strategy and analyzed with a t-test and analysis of variance (ANOVA). The results showed that gen-der had a significant effect on food involvement: female respondents had a higher tendency to become culinary tourists and had higher food involvement than male respondents. Education also proved to be an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The educational level may determine tourists' behavior in specific tourism experiences and be associated with other factors. For example, Okumus et al [27] confirmed that tourists with a higher level of education were more willing to participate in culinary tourism experiences compared to visitors with a basic level of education.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The educational level may determine tourists' behavior in specific tourism experiences and be associated with other factors. For example, Okumus et al [27] confirmed that tourists with a higher level of education were more willing to participate in culinary tourism experiences compared to visitors with a basic level of education.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [26] examined the perceptions of homestay guests and found that gender, age, and educational level influenced the perceived value of the experience at the functional, emotional, and social levels. Okumus et al [27], in the context of food tourism, found that age, gender, and education level strongly influenced food awareness and involvement in culinary experiences.…”
Section: Influence Of Demographic Variables On the Behavior Of Experi...mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, residents' negative tourism perceptions reduce support for tourism development (García et al , 2015; Lankford and Howard, 1994). However, to understand local tourism support in more detail, demographic factors can be functional in understanding behavioral trends (Mattson and Ruther, 2012; Okumus et al , 2021), attitudes (Marafa and Tung, 2004) and social embeddedness (Bowker, 1983). At this point, it is useful to better understand residents' perceptions of tourism impacts and their attitudes toward tourism support while examining demographic factors in this context.…”
Section: Introductionmentioning
confidence: 99%